An experimental study of the influence of process parameters on the textile reaction to transverse impregnation. Issue 9 (28th March 2015) - Becker, D.; Broser, J.; Mitschang, P.
Abstract : When applying a transverse impregnation within a liquid composite molding process, the main goal is to decrease impregnation time by reducing flow path lengths within the textile. However, the pressure drops emerging during impregnation cause hydrodynamic compaction of the textile as well as a heterogenization of the fiber volume content distribution. Within this study a new approach for the description of such transverse impregnation behavior is presented and exemplarily shown for a woven and a noncrimp fabric. The starting point is a novel measurement system allowing an on‐line monitoring of flow‐induced compaction during permeability measurement. Using the system, the reaction of both textiles to various flow conditions in terms of pressure drop and flow rate was measured and expressed by a set of functions. These allow continuous interpolation and can be used e.g. as direct input for simulations or to validate existing models. For both textiles a severe reduction of the permeability with increasing pressure drop respectively flow rate was measured. Accordingly, it was found that with increasing injection pressure the flow rate can stagnate or even decrease. Knowledge about such behavior is required for process and tooling optimization concerning cycle‐time and cost‐efficiency. POLYM. COMPOS., 37:2820–2831, 2016. © 2015 Society of Plastics Engineers